Strategi pengembangan agroindustri kopi robusta kelompok tani sumber kembang di Kabupaten Jember - Ikhwan Samsul Hadi Sidiq; Bambang Herry Purnomo; Sony Suwasono; Djoko Soemarno (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Kelompok Tani Sumber Kembang (KTSK) is a community organization of farmer’s coffee around the Argopuro. KTSK was formed to benefit the community. Still, there are several problems, namely the low quality of the coffee, relatively simple technology, familial institutions, low human resource skills, and limited capital. This research was conducted to create a coffee agroindustry development strategy in Jember. The research methods used the ISM and AHP methods. Interpretive Structural Modeling (ISM) produces critical sub-elements in the elements of objectives, constraints, actors, activities, and the needs for the development of the coffee agroindustry. AHP method is used to generate development strategy priorities. The results of this research are the key sub-elements, namely the development of an agropolitan area with a model of integration of the upstream and downstream industries. Farmers' institutional development needs to be improved to make a good synergy between coffee farmers, Puslit Koka and Perhutani. This provides recommendations for decision-makers in planning the development of the coffee agroindustry